Reluctant shamans: on the limits of human agency and the power of partible souls among the Kham Magars of Nepal - Zharkevich, I (Routledge, 2024)
This chapter is based on a series of encounters with the Kham Magar novice shamans, men and women, young and old, whose narratives indicated a considerable degree of resistance towards the career of a shaman and suffering in the process of becoming one. To them, the power of the invisible world and particularly of the ancestral spirits was incommensurately higher than that of humans, for when afflicted by the spirit of deceased shaman even a long-term Christian had to “convert” to shamanism in order to “survive”. In explaining the situation of becoming a shaman against one’s will, the chapter turns to the Kham Magar concept of the soul, which underpins the relationships of humans with the invisible world and its inhabitants. The soul, 22 hamsa and 22 purusha, is not singular, but rather multiple and partible. The paper will show how the concept of the partible soul helps to elucidate not only the phenomenon of “reluctant” shamans and “reluctant witches” against whom the shamans are fighting, but also the supremacy of the invisible world in structuring the world that is visible.